Vision-related quality of life in patients with a history of congenital glaucoma. Issue 6 (November 2021) - Miraftabi, Arezoo; Coleman, Anne L; Nilforushan, Naveed; Parsamanesh, Mohammad; Nguyen, Andrew H; Karimi, Nasser; Chibaksh, Samira
Purpose: To assess the vision-related quality of life in adult patients with a history of primary congenital glaucoma. Methods: In a cross-sectional hospital-based study eligible patients with a history of primary congenital glaucoma aged more than 18 were recruited in the study. Patients with secondary glaucoma and monocular patients were excluded. All patients underwent a complete ophthalmologic examination. The subjects were requested to answer a Persian approved version of the 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25) questionnaire. Results: A total of 23 congenital glaucoma patients have enrolled in the study. The mean age was 29.22 (9.3 SD) and mean IOP was 13.82 (5.19 SD) and 15.69 (5.26 SD) in right and left eyes, respectively. The mean number of medications was 1.13 (1.25 SD) in the right and 1.30 (1.18 SD) in the left eyes. Among all scores of NEI-VFQ-25, the lowest score belonged to mental health 53.71 (29.72) and the highest score was color vision score 83.69 (20.79). We found a significant influence of visual field defect on many subscales including general health and general vision ( p = 0.007, R = +0.65) and ( p = 0.002, R = +0.71) respectively. The Mean Defect (MD) was associated with low social functioning and peripheral vision too ( p = 0.035, R = +0.53) and ( p = 0.001, R = +0.76) respectively. Age had a negative impact on the general vision subscale ( p = 0.003, R = −0.59). Conclusion: Our study showed that visual field defect was strongly associated with many subscales scores in (NEI VFQ-25) questionnaire.